1971
DOI: 10.1111/j.1365-2621.1971.tb02059.x
|View full text |Cite
|
Sign up to set email alerts
|

Texture of Semi‐solid Foods: Sensory and Physical Correlates

Abstract: SUMMARY– Texture profile analyses (TPA) were conducted on a series of commercial desserts (puddings, custards, and gelatin) and on whipped toppings and marshmallow creme. Textural attributes of firmness, elasticity, cohesiveness, gumminess, and chewiness were determined on each product, (a) under compression as in conventional TPA, and (b) under tension to provide five new additional textural parameters. They are referred to as firmness under compression (Fc), firmness under tension (FA), elasticity under comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

1976
1976
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 16 publications
1
22
0
1
Order By: Relevance
“…The reason for this may be that this method has usually been applied only to semi-solid foods (Friedman et al, 1963, Henry et al, 1971, and minced fish could be considered to belong to this category. However, when applying this compression method to an item with a layered structure like fish fillets, the myotomes layers tend to slide away from the force of compression, thus making it impossible to reproduce the analysis results in different tests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this may be that this method has usually been applied only to semi-solid foods (Friedman et al, 1963, Henry et al, 1971, and minced fish could be considered to belong to this category. However, when applying this compression method to an item with a layered structure like fish fillets, the myotomes layers tend to slide away from the force of compression, thus making it impossible to reproduce the analysis results in different tests.…”
Section: Resultsmentioning
confidence: 99%
“…Compression: The measurements were taken with a compression assembly. Compression analysis was applied in order to obtain values for firmness, cohesiveness, and elasticity (Friedman, Whitney & Szczesniak, 1963;Henry et al, 1971), relaxation (Stanley, Pearson & Coxworth, 1971) and the modulus of elasticity (Moskowitz & Kapsalis, 1976). Juiciness was also evaluated by compression by placing a sufficient amount of filter paper on both sides of the sample to collect the juice pressed out on application of a constant force of 25 kg for 1 min.…”
Section: Instrumental Methodsmentioning
confidence: 99%
“…They concluded that for the gels tested, Szczesniak's five primary mechanical characteristics could be reduced to three: springiness, adhesiveness, and viscosity. Henry et al (1971) evaluated the texture of semi-solid foods instrumentally and sensorially. They concluded that 15 sensory attributes of texture could be reduced to four factors; namely, "firm and frangible," "stringy and sticky," "fat-like," and "grainy" factors accounting for more than 90% of the original variance.…”
Section: Introductionmentioning
confidence: 99%
“…Texture parameters were determined by means of texture profile analysis (TPA) (Bourne, 1978;Henry, Katz, Pilgrim & May, 1971). Measurements were taken at room temperature, with a TA-XT2 Texture Analyser (Stable Micro Systems, Godalming, UK) with a load cell of 5 kg.…”
Section: Texture Analysismentioning
confidence: 99%